A cucurbituril/polysaccharide/carbazole ternary supramolecular assembly for targeted cell imaging. Issue 30 (26th March 2019) - Wu, Xuan; Chen, Yong; Yu, Qilin; Li, Feng-Qing; Liu, Yu
Abstract : A ternary supramolecular assembly with near-infrared lysosome imaging and targeted photodynamic therapy properties was successfully orthogonally constructed in a two-step assembly manner. Abstract : A carbazole derivative (G ) was synthesized as a photosensitizer to complex with cucurbit[8]uril, resulting in a nanocube with emission at 662 nm for lysosome cell imaging. Furthermore, the alkyl chain onG was included by α-cyclodextrine-modified hyaluronic acid for further assembly, affording a system targeted to cancer cells.